Mode Choice Modelling to Shift Car Travelers Towards Park and Ride Service in the CBD of Putrajaya and Karachi - MEMON, IRFAN AHMED (2018)
The imbalance between the usage of public and private transportation creates traffic congestion. Consequently, traffic congestion is expanding up to the outskirts of the city. centres during peak hours. Currently, congestion in Karachi’s and Putrajaya’s central business districts (CBD) is the result of people driving their cars to work. Therefore, being a part of travel demand management (TDM), park and ride (P&R) service has been extensively used in many countries.